Radiographic classification and treatment of fibrous dysplasia of the proximal femur: 227 femurs with a mean follow-up of 6 years - Zhang, Xuelei (J Orthop Surg Res, 2015)
BACKGROUND: Research into the optimal treatment of fibrous dysplasia has been limited by the lack of an established classification system for the disease. The purposes of this study were to develop a radiographic classification for fibrous dysplasia of the proximal femur and to test this classification’s intra- and interobserver reliability as well as the effectiveness of our treatments. METHODS: We retrospectively reviewed radiographs and computed tomography (CT) of 227 femurs from 206 patients with fibrous dysplasia. The radiographs were evaluated in the coronal plane for neck-shaft angle, varus deformity in the proximal femoral shaft, and distal juxtaarticular valgus deformity. CT was evaluated in the axial plane for destruction of cortex. Reduction of bone strength was defined as the thickness of the remaining cortex less than 50 % of the original on axial CT. Two senior orthopedists evaluated each radiograph and CT twice at 8-week intervals. Intra- and interobserver reliability testing was performed using the kappa statistic. Treatments were assessed through mid-term follow-up. RESULTS: The 227 femurs were classified into five reproducible types: type 1 (33 %), normal bone strength without angular deformity; type 2 (30 %), decreased bone strength without angular deformity; type 3 (12 %), isolated coxa vara with neck-shaft angle <120°; type 4 (11 %), isolated varus deformity in the proximal femoral shaft; and type 5 (14 %), coxa vara with varus deformity in the proximal femoral shaft. Intra- and interobserver kappa values were excellent, ranging from 0.85 to 0.88. Good clinical outcomes were achieved. CONCLUSIONS: This radiographic classification of fibrous dysplasia is reproducible and useful for describing and assessing this disease. The treatments based on this classification were effective.